The timing of cyclic cytotoxic chemotherapy can worsen neutropenia and neutrophilia. Issue 2 (30th June 2020) - Mackey, Michael C.; Glisovic, Sanja; Leclerc, Jean‐Marie; Pastore, Yves; Krajinovic, Maja; Craig, Morgan
Abstract : Despite recent advances in immunotherapies, cytotoxic chemotherapy continues to be a first‐line treatment option for the majority of cancers. Unfortunately, a common side effect in patients undergoing chemotherapy treatment is neutropenia. To mitigate the risk of neutropenia and febrile neutropenia, prophylactic treatment with granulocyte‐colony stimulating factor (G‐CSF) is administered. Extensive pharmacokinetic/pharmacodynamic modelling of myelosuppression during chemotherapy has suggested avenues for therapy optimization to mitigate this neutropenia. However, the issue of resonance, whereby neutrophil oscillations are induced by the periodic administration of cytotoxic chemotherapy and the coadministration of G‐CSF, potentially aggravating a patient's neutropenic/neutrophilic status, is not well‐characterized in the clinical literature. Here, through analysis of neutrophil data from young acute lymphoblastic leukaemia patients, we find that resonance is occurring during cyclic chemotherapy treatment in 26% of these patients. Motivated by these data and our previous modelling studies on adult lymphoma patients, we examined resonance during treatment with or without G‐CSF. Using our quantitative systems pharmacology model of granulopoiesis, we show that the timing of cyclic chemotherapy can worsen neutropenia or neutrophilia, and suggest clinically‐actionable schedules to reduce the resonant effect. We emphasize that delaying supportive G‐CSF therapy to 6–7 days after chemotherapy can mitigate myelosuppressive effects. This study therefore highlights the importance of quantitative systems pharmacology for the clinical practice for developing rational therapeutic strategies.